2008
DOI: 10.1001/archotol.134.4.403
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SLC26A4 (PDS) Deafness Mutation Retained in the Endoplasmic Reticulum

Abstract: To identify mutations in the SLC26A4 gene in individuals with nonsyndromic hearing loss and enlarged vestibular aqueduct, to design a predicted model of the pendrin protein, and to characterize novel mutations by means of localization in mammalian cells and effect of the mutation on the predicted model. Design: Validation of the mutation by its exclusion in more than 300 individuals with normal hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Among another family with three offspring with compound R409H/ 1561_1571CTTGGAATGGC PS mutations, extreme variability was observed, both for the degree of impairment and the age of onset [29]. These findings are supported by localization assays, where retention of pendrin in the endoplasmic reticulum (ER) was observed, rather than targeting to the plasma membrane, for mutations involved in PS, including L236P, T416P, G384E and V239D [30,31] as well as for mutations associated with NSHL, including T410M, Q446R and c.1458_1459insT [14,32].…”
Section: Slc26a4 (Pds) Deafness Mutationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Among another family with three offspring with compound R409H/ 1561_1571CTTGGAATGGC PS mutations, extreme variability was observed, both for the degree of impairment and the age of onset [29]. These findings are supported by localization assays, where retention of pendrin in the endoplasmic reticulum (ER) was observed, rather than targeting to the plasma membrane, for mutations involved in PS, including L236P, T416P, G384E and V239D [30,31] as well as for mutations associated with NSHL, including T410M, Q446R and c.1458_1459insT [14,32].…”
Section: Slc26a4 (Pds) Deafness Mutationsmentioning
confidence: 86%
“…Functional assays have shown that different mutations within the SLC26A4 sequence have different effects on pendrin transport activity [12]. Furthermore, whereas the number of pendrin transmembrane domains is still ambiguous in the literature [13], it is clear that some of the mutations affect pendrin sub-cellular localization so that pendrin fails to reach the plasma membrane [14]. Thus, the variable effect of each mutation on pendrin function, expression and localization can explain some of the clinical heterogeneity observed among affected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The c.1458_1459insT mutation of the SLC26A4 gene was detected in a Jewish Iranian proband with NSHL and EVA after excluding mutations in Cx26 (17). The deaf individual had progressive postlingual HL that began at age 6 and progressed to profound deafness.…”
Section: Autosomal Recessive Gene Slc26a4mentioning
confidence: 96%
“…Both the connexin encoding genes, GJB2 and GJB6, are involved in 31% of NSHL in the Jewish Israeli population studied. Two more genes, MYO3A (encoding myosin IIIA) (16) and SLC26A4 (encoding pendrin) (17), are involved in autosomal recessive deafness, and one gene, POU4F3 (18), is associated with autosomal dominant HL. In addition, one dominant gene has been mapped for otosclerosis, OTSC4 (19).…”
Section: Deafness Genes In the Jewish Israeli Populationmentioning
confidence: 99%
See 1 more Smart Citation